Personnel administration : a point of view and administration - Pigors, Paul.; Myers, Charles A. (London; Toronto : McGraw-Hill Book company, 1959)
The aims which have characterized every edition of this text are to offer (and illustrate) ideas that can be useful not only to students, but also to practitioners, both staff and line, with responsibility for personnel relations, and to emphasize (and illustrate) the concept that although personnel administration is staff function ,it is ultimately a line responsibility.
Includes bibliographical references and index.
hza 19/07/2018
Loans
Keywords: Personnel management